Emmy and the Home for Troubled Girls - Jonell, Lynne (Henry Holt and Co., 2008)
Ten-year-old Emmy wants to be an ordinary girl, but the evil nanny Miss Barmy, now a rat, has trapped five of her former charges and when she uses them to steal jewels belonging to Emmy's parents, it is up to Emmy, Joe, and their rodent friends to stop her.